Intellectual, Mnemonic, and Frontal Functions in Dementia with Lewy Bodies: A Comparison with Early and Advanced Parkinson’s Disease - John Joseph Downes; Nicholas M. Priestley; Mark Doran; Jose Ferran; Eric Ghadiali; Paul Cooper (Behavioural Neurology)
Both Parkinson’s disease (PD) and dementia with Lewy bodies (DLB) share a common neuropathological marker, the presence of Lewy bodies in brain stem and basal forebrain nuclei. DLB, in addition, is associated with Lewy bodies in the neocortex, and, in it’s more common form, with Alzheimer-type pathological markers, particularly amyloid plaques. Published neuropsychological studies have focused on the differential profiles of DLB and Alzheimer’s disease (AD). However, it is presently unclear whether DLB should be classified as a variant of AD or PD. In the present study we compare a healthy age-matched control group with three groups of patients, one with DLB, and two with PD. One of the PD groups was early in the course (PD-E) and the second, more advanced group (PD-A), was matched on severity of cognitive impairment with the DLB group. The results show that DLB was associated with a different pattern of neuropsychological impairment than the PD-A group, particularly in tests believed to be mediated by prefrontal cortical regions.